2022
DOI: 10.1002/chem.202104004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Hydroboration of Imines from Combined Computational and Experimental Studies

Abstract: Boron Lewis acid‐catalyzed and catalyst‐free hydroboration reactions of imines are attractive due to the mild reaction conditions. In this work, the mechanistic details of the hydroboration reactions of two different kinds of imines with pinacolborane (HBpin) are investigated by combining density functional theory calculations and some experimental studies. For the hydroboration reaction of N‐(α‐methylbenzylidene)aniline catalyzed by tris[3,5‐bis(trifluoromethyl)phenyl]borane (BArF3), our calculations show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…Given the multiple mechanistic pathways for the reaction, DFT analysis [M06-2X/6-311++G(d,p)] [41,42] was used to differentiate between these two pathways. 9-Borabicyclo [3.3.1]nonane ([H-B-9-BBN] 2 ) was chosen as the catalyst for the calculations due to its comparable activity to H 3 B•SMe 2 (Scheme 3b) and the reduced number of reactive B-H sites to reduce complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Given the multiple mechanistic pathways for the reaction, DFT analysis [M06-2X/6-311++G(d,p)] [41,42] was used to differentiate between these two pathways. 9-Borabicyclo [3.3.1]nonane ([H-B-9-BBN] 2 ) was chosen as the catalyst for the calculations due to its comparable activity to H 3 B•SMe 2 (Scheme 3b) and the reduced number of reactive B-H sites to reduce complexity.…”
Section: Resultsmentioning
confidence: 99%
“…The -ate complex 17, generated from diboron and base NaO t Bu, reacted with complex 16 to provide a key intermediate ( 18) (Scheme 4b). Selective addition of alkynes (14) to the intermediate (18) led to the formation of a vinylboronate intermediate (19). In the next step, EtOH acted as the source of hydrogen to generate the product 15 and I(III) species (20).…”
Section: Hydroboration Of Alkynesmentioning
confidence: 99%
“…The reduction of unsaturated CÀ C and CÀ X bonds results in the formation of highly reactive vinyl or alkyl boronates that are well-known coupling reagents for cross-coupling reactions [10][11][12] and convenient precursors for obtaining alcohols and amines. [13][14][15][16][17][18] This groundbreaking elementary reaction, reported by Brown et al [19][20][21] more than 60 years ago, showed the importance of the hydroboration reaction and nature of boroncontaining compounds. Starting from this discovery, follow-up hydroboration reactions made use of stoichiometric hydroboranes from simple diborane ((BH 3 ) 2 ) to various borane adducts and borohydrides.…”
Section: Introductionmentioning
confidence: 96%
“…We hypothesised that NaHBEt 3 not only serves to reduce the metal centre and clear it of chlorine atoms, but also deprotonates the NH groups present in the heterocyclic units of the ligand and binds to nitrogen atoms – that is why Fe-L1 and Fe-L4 , as well as Co-L1 and Co-L4 have significantly different activities. 22 In order to verify our hypothesis we conducted a series of 1 H and 11 B NMR experiments (see the ESI† for details). First we added NaHBEt 3 to L1 in THF- d 8 and the 1 H NMR results showed swift deprotonation of NH units.…”
mentioning
confidence: 99%